2021
DOI: 10.1177/1558925021988976
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the seam strength of denim garments by using fuzzy expert system

Abstract: The main purpose of this study is to predict and develop a model for forecasting the Seam Strength (SS) of denim garments with respect to the thread linear density (tex) and Stitches Per Inch (SPI) by using a Fuzzy Logic Expert System (FLES). The seam strength is an important factor for the serviceability of any garments. As seams bound the fabric pieces together in a garment, the seams must have sufficient strength to execute this property even in the unexpected severe conditions where the garments are subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…if-then rules are used to represent the knowledge in a knowledge base system. These if-the statements relate the input variables and output variables [ 53 , 61 ]. Fuzzy rules base is classified as Mamdani and Sugeno [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…if-then rules are used to represent the knowledge in a knowledge base system. These if-the statements relate the input variables and output variables [ 53 , 61 ]. Fuzzy rules base is classified as Mamdani and Sugeno [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Though ANN models usually require a huge number of datasets to operate accurately, at the same time if designed optimum, it can also demonstrate an excellent accuracy with a small amount of dataset [ 47 ]. On the other hand, fuzzy logic-based models are simple, require less data, cheaper in design cost, and are highly configurable [ 36 , 53 , 54 ]. Furthermore, the fuzzy logic-based model excels at property prediction, particularly with fewer datasets, which is beneficial for the industries [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters have to be maintained in order to maximize the product durability by ensuring a proper interaction between the fabrics and the seam [6][7][8]. Yassen studied the effect of sewing thread count, sewing needle size, stitch density, and fabric properties on seam strength and showed that both sewing and fabric parameters had a substantial impact on seam strength [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among different soft computing-based approaches, the fuzzy inference-based prediction system has been successfully developed and utilized in the prediction of different fabric properties [ 25 , 31 , 32 , 33 , 34 ]. Besides, the color property [ 35 , 36 ], tearing strength, and seam strength of the garments [ 37 , 38 ] have also been predicted using the fuzzy inference-based prediction system. Although the fuzzy logic-based models exhibited excellent performance in most cases, it primarily relies on expert suggested rule base system, which can be subjective depending upon the expert.…”
Section: Introductionmentioning
confidence: 99%